Topos y Dramaturgia - Grabocz, Marta; Leongomez Herrera, (Traducción) Alberto ((pensamiento) (palabra)... Y obra, 2013)
“Topoi and dramaturgy”: analysis of the meanings and the expressive strategy in two symphonic movements of Bela Bartok (Two images Op. 10/ I “in full bloom” and the adagio of the Music for strings, percussion and celesta)